Low flow in the left atrial appendage assessed by transesophageal echocardiography is associated with increased stroke severity—Results of a single-center cross-sectional study. Issue 4 (June 2019) - Schnieder, Marlena; Siddiqui, Tariq; Karch, André; Bähr, Mathias; Hasenfuß, Gerd; Schroeter, Marco R; Liman, Jan
Background: About 25% of strokes are thought to be cryptogenic. There is growing evidence that most of these cryptogenic strokes are thromboembolic and caused by an undetected atrial fibrillation. Measured slow flow in the left atrial appendage has been proposed to be an indicator for the thromboembolic risk since it is possibly associated with undetected atrial fibrillation. Methods: We evaluated all patients (n = 909; mean of 62 years, 39% female) admitted with an ischemic stroke (84%) or transient ischemic attack to our university medical center who underwent transesophageal echocardiography examination 2012–2014. Baseline characteristics, cardio-/neurovascular risk factors, electrocardiogram monitoring data, National Institute of Health Stroke Scale values, the localization of the stroke, as well as transesophageal echocardiography findings were analyzed. Results: Stroke severity measured by the National Institute of Health Stroke Scale in patients with a low flow in the left atrial appendage was significantly higher than in patients without left atrial appendage low flow (p < 0.001). There was a threshold phenomenon in flow velocity at about 60 cm/s above which no significant change in National Institute of Health Stroke Scale values could be observed. These patients were significantly different concerning incidence of heart failure (10.6% vs. 2.3%; p < 0.001) and atrial fibrillation (32.2% vs. 8.8%; p < 0.001). However, threshold phenomenon of left atrial appendage flow was unchanged when excluding atrial fibrillation and heart failure patients. Conclusions: A low flow in the left atrial appendage was associated with clinically elevated stroke severity and could be indicated as an independent stroke risk factor. Further prospective studies are warranted to evaluate beneficial effects of therapeutic options in these patients also in the assumed absence of atrial fibrillation.